DAMPAK KUALITAS PRODUK, CITRA MEREK DAN PROMOSI DALAM MENCIPTAKAN KEPUTUSAN PEMBELIAN SMARTPHONE SAMSUNG - Riani, Rizka; Saputra, Cikal Krisna; Octavia, Ayu Nurafni (JURNAL PUNDI, 2024)
This research is motivated by increasingly fierce technological competition, so companies are required to maintain the existence of their products. The aim of this research is to determine the influence of product quality, brand image, and promotion on Samsung smartphone purchasing decisions. This research uses a questionnaire method distributed to Samsung smartphone users with a sample size of 96 respondents. The sampling technique used in this research is non-probability sampling. The analytical tool used in this research is multiple linear regression analysis, where validity tests, reliability tests, and classical assumption tests have previously been carried out. The results of this research show that product diversity has a positive and significant effect on purchasing decisions; this shows that the better the product quality, the more purchasing decisions. Brand image has a positive and significant effect on purchasing decisions; this shows that the better the brand image will increase purchasing decisions. Promotion has a positive and significant effect on purchasing decisions. This shows that the more frequently a product is promoted, the more purchasing decisions it will increase. Simultaneously, product quality, brand image, and promotion have a positive and significant effect on Samsung smartphone purchasing decisions